Role of aspirin-triggered lipoxin A4, aspirin, and salicylic acid in the modulation of the oxidative and inflammatory responses induced by plasma from women with pre-eclampsia (2019)
Problem Oxidative stress and inflammation are key events leading to pre-eclampsia, involved in several maternal deaths. Low doses of acetylsalicylic acid (ASA) are used in the prevention and treatment of pre-eclampsia. The synthesis of aspirin-triggered lipoxin (ATL) by cyclooxygenase-2 acetylation is an alternative mechanism of ASA, which could explain the effectiveness of ASA treatments. The aim of this study was to evaluate the role of ASA, salicylates, and ATL in the modulation of the oxidative and inflammatory responses induced by plasma from women with pre-eclampsia. Method of study Plasma from 14 women with pre-eclampsia and 17 normotensive pregnant women was probed for inducing oxidative and inflammatory responses on endothelial cells and U937 promonocytes. The role of ATL, ASA, and salicylic acid (SA) on these events was evaluated. Results Plasma from women with pre-eclampsia induced TBARS and nitrotyrosine production on endothelial and U937 cells. Pre-treatment with both ATL and ASA decreased the TBARS production, while ATL decreased the nitrotyrosine. Pre-eclamptic plasma augmented the translocation of NF-kB on U937 cells, which decreased by a high dose of ASA and SA. Finally, the pre-eclamptic plasma increased the adhesion of leukocytes—PMN and monocytes—to endothelium, and we were able to determine a state of resolution of inflammation, since ATL decreased the PMN adhesion, and conversely, it increased the monocytes adhesion to endothelium. Conclusion Together, these results suggest that ATL could explain the beneficial actions of ASA and support further research on mechanisms, real efficacy, and rational use of ASA in pre-eclampsia.